The influence of peri-operative factors for accelerated discharge following laparoscopic colorectal surgery when combined with an enhanced recovery after surgery (ERAS) pathway. (January 2016) - Chand, Manish; De'Ath, Henry D.; Rasheed, Shahnawaz; Mehta, Chaitanya; Bromilow, James; Qureshi, Tahseen
Abstract: Introduction: Laparoscopic surgery is well established in the modern management of colorectal disease. More recently, enhanced recovery after surgery (ERAS) protocols have been introduced to further promote accelerated discharge and faster recovery. However, not all patients are suitable for early discharge. The purpose of this study was to evaluate the early outcomes of patients undergoing such a regime to determine which peri-operative factors may predict safe accelerated discharge. Methods: Data were prospectively collected on consecutive patients undergoing laparoscopic colorectal surgery. All patients followed the institution's ERAS protocol and were discharged once specific criteria were fulfilled. Clinical characteristics and outcomes were compared between patients who were discharged before and after 72 h post-surgery. Thereafter, the peri-operative factors that were associated with delayed discharge were determined using a binary logistic model. Results: Three hundred patients were included in the analysis. The most common operation was laparoscopic anterior resection (n = 123, 41%). Mean length of stay was 4.8 days (standard deviation 5.9), with 185 (62%) patients discharged within 72 h. Ten (3%) patients had a post-operative complication. Three independent predictors of delayed discharge were identified; BMI (OR 1.06, 95%CI 1.01–1.11), operation length (OR 0.99, 95%CI 0.98–0.99) and complications (OR 16.26, 95%CI 4.88–54.08). Conclusions: A combined approach of laparoscopic surgery and ERAS leads to reduced length of stay. This enables more than 60% of patients to be discharged within 72 h. Increased BMI, duration of operation and complications post-operatively independently predict a longer length of stay. Highlights: We present a series of laparoscopic colorectal resections combined with ERAS. Overall, laparoscopic surgery and ERAS combined led to safe early discharge. Higher BMI, operation duration and complications predicted longer length of stay.